혁신의 제도적 접근: 지역혁신체제와 혁신클러스터의 지식파급효과-선행연구의 검토와 새로운 쟁점 - 배응환; Eong Hwan Bae (한국경제지리학회지, 2015)
세방화시대에 모든 국가의 공통현상은 국가와 지역차원에서 지식혁신과 성장이 중요한 화두로 등장하여 이론과 실제에서 연구되고 있다. 선진국에서 지역발전의 성공사례에서는 지역혁신체제와 클러스터가 혁신을 주도하고 있다. 이에 지역혁신체제의 축소모형인 혁신클러스터에서의 지식파급효과가 기업혁신과 지역성장을 유도하는지를 분석하는 것은 중요하다. 본 연구는 혁신지리학의 지역혁신체제와 혁신클러스터에서의 지식파급효과에 대한 이론적 논의와 경험적 연구흐름을 비판적으로 검토한 후, 보다 심화된 연구를 위한 연구쟁점을 제시한 것이다. 분석결과, 선행연구들은 지식파급효과가 특정한 지리적 근접성의 지식집약산업에서 존재한다고 인식하고 지역혁신을 위해서는 순수지식파급효과가 중요하다고 한다. 그러나 선행연구의 한계로는 제한된 지리적 공간과 기술영역, 소수의 분석변수 그리고 렌트파급효과무시 등이 있다. 따라서 지식파급효과와 관련한 새로운 연구쟁점으로는 지리적 차원(지역과 글로벌), 기술적 차원(다양한 지식기반산업), 분석변수의 다양화(종전의 변수 외에 시간이나 사회자본), 개념화(무단사용과 기술시장) 등을 들 수 있다. In the glocalization a common phenomenon of several nations reveals knowledge innovation and growth by the important subject of region and state and is studied at theory and practice. the successful cases of regional development in an advanced country have leading innovation through regional innovation system and cluster. therefore we are necessary to analyse how the knowledge spillovers in innovative cluster as the reduced model of regional innovation system guide firm innovation and region growth. this article reviews theories and empirical studies of the knowledge spillovers in the regional innovation system and innovative cluster of innovative geography and proposes a new research issues for further explorations of the knowledge spillovers. Previous studies assist that knowledge spillovers exist in knowledge-based industries of specific local area and local innovation accomplishes through pure knowledge spillover. but limits of these studies include narrow region and technological area, few analytical variable and exclusion of rent knowledge spillover. therefore new research topics related with that exemplifies geographical dimension(concentration and decentralization), technological dimension(knowledge based industry), category of analytic variables(previous indicators, time, and social capital), conceptualization(appropriation means, markets for technology) etc.